Refinement of Global Domestic Horse Biogeography Using Historic Landrace Chinese Mongolian Populations. (19th October 2019) - Han, Haige; Bryan, Kenneth; Shiraigol, Wunierfu; Bai, Dongyi; Zhao, Yiping; Bao, Wuyingga; Yang, Siqin; Zhang, Wengang; MacHugh, David E; Dugarjaviin, Manglai; Hill, Emmeline W
Abstract: The Mongolian horse is one of the oldest extant horse populations and although domesticated, most animals are free-ranging and experience minimal human intervention. As an ancient population originating in one of the key domestication centers, the Mongolian horse may play a key role in understanding the origins and recent evolutionary history of horses. Here we describe an analysis of high-density genome-wide single-nucleotide polymorphism (SNP) data in 40 globally dispersed horse populations ( n = 895). In particular, we have focused on new results from Chinese Mongolian horses ( n = 100) that represent 5 distinct populations. These animals were genotyped for 670K SNPs and the data were analyzed in conjunction with 35K SNP data for 35 distinct breeds. Analyses of these integrated SNP data sets demonstrated that the Chinese Mongolian populations were genetically distinct from other modern horse populations. In addition, compared to other domestic horse breeds, the Chinese Mongolian horse populations exhibited relatively high genomic diversity. These results suggest that, in genetic terms, extant Chinese Mongolian horses may be the most similar modern populations to the animals originally domesticated in this region of Asia. Chinese Mongolian horse populations may therefore retain ancestral genetic variants from the earliest domesticates. Further genomic characterization of these populations in conjunction with archaeogenetic sequence data should be prioritized for understanding recent horse evolution and the domestication process that has led to the wealth of diversity observed in modern global horse breeds.